Characteristics and timeliness of intervention in 47 school-based enterovirus outbreaks in Zhejiang Province, China - Chen, Yijuan; Sun, Wanwan; Ren, Xiaobin; Gu, Xiaomin; Song, Kai; Wang, Pingping; Cao, Yanli; Jiang, Jianmin; Miao, Ziping (Frontiers in Public Health, 2025)
BackgroundHand, foot, and mouth disease (HFMD) and herpangina (HA) are common infectious diseases in children that can frequently lead to outbreaks. Analyzing the characteristics of school-based outbreaks and evaluating the timeliness of prevention and control measures can provide valuable insight for early identification, timely warnings, and the development of prevention strategies.MethodsThis study collected data on HFMD and HA outbreaks in Zhejiang Province from 2021 to 2023, providing a comprehensive analysis of the pathogen spectrum, epidemiology, and clinical characteristics of each outbreak. A generalized linear model with a Poisson distribution was used to assess the impact of various intervention timings on the effectiveness of disease control.ResultsBetween 2021 and 2023, a total of 47 HFMD and HA outbreaks were reported in Zhejiang Province, spanning eight cities and 28 counties. Specifically, six HA outbreaks were reported in one city and three counties, 31 HFMD outbreaks occurred across eight cities and 22 counties, and ten mixed HFMD-HA outbreaks were identified in four cities and six counties. Herpangina outbreaks were confined to 2021, whereas HFMD outbreaks occurred annually. Nearly all outbreaks (93.62%) occurred in educational or childcare settings. The predominant strain of HFMD shifted from CVA16 in 2021 and 2022 to CVA6 in 2023, while CVA4 was primarily associated with HA. Seasonally, HA outbreaks peaked between April and May, whereas HFMD outbreaks transitioned from a broader March–October season to a narrower May–June period. Clinically, HA cases exhibited a higher proportion of fever, oral herpes, and sore throat compared to HFMD cases (p < 0.05). Outbreak duration was positively correlated with the number of cases, with each additional day of outbreak duration leading to a 6.6% increase in case numbers. Similarly, delays in implementing class suspensions were associated with larger outbreaks, with each day’s delay resulting in a 5.0% increase in cases numbers.ConclusionDifferent enteroviruses are responsible for HFMD and HA outbreaks, with childcare facilities frequently acting as key hotspots. Timely case isolation and the implementation of effective management strategies are crucial for controlling the transmission dynamics of these diseases.